Metals and Metalloid Removal by Colloidal Humic Acid–Goethite: Column Experiments and Geochemical Modeling - Montalvo, D. (2020)
This study was set up to measure interactions during reactive transport of the anionic arsenate As(V) and cationic metals and test if that transport can be modeled with geochemical codes. Sand coated with colloidal humic acid–goethite was the adsorbent in line with field work where these colloidal particles have been injected in situ. Equilibrium batch adsorption experiments showed binding preferences in the order: As(V) ∼ Cu >> Zn > Cd > Ni. Column experiments with single and binary mixtures showed an important synergistic effect of As(V) on Zn sorption but the reverse interaction was not found; this interaction is not included in the PHREEQC geochemical code. The breakthrough curves (BTCs) of mixtures of As(V), Cd, Cu, Ni, and Zn showed that Cd and Ni concentrations in the effluent exceeded those of the influent, an overshooting effect attributed to competition among divalent cations. Simulations with the PHREEQC geochemical code using a surface complexation model for sorption reactions on goethite and humic acids coupled to the transport module successfully predicted the most essential trends of the BTCs, illustrating the potential of these codes to estimate the longevity of the reactive barriers used to remediate mixtures of contaminants. The novel aspect of this work is that a correct reactive transport model in PHREEQC was obtained by only adjusting the number of reactive surface sites of the adsorbent from fitting batch sorption distribution coefficient (Kd) values.